Correcting Finger Counting to Snellen Acuity. (2nd September 2016) - Karanjia, Rustum; Hwang, Tiffany Jean; Chen, Alexander Francis; Pouw, Andrew; Tian, Jack J.; Chu, Edward R.; Wang, Michelle Y.; Tran, Jeffrey Show; Sadun, Alfredo A.
ABSTRACT: In this paper, the authors describe an online tool with which to convert and thus quantify count finger measurements of visual acuity into Snellen equivalents. It is hoped that this tool allows for the re-interpretation of retrospectively collected data that provide visual acuity in terms of qualitative count finger measurements.